2012
DOI: 10.1177/0263276411427409
|View full text |Cite
|
Sign up to set email alerts
|

Investing in Life, Investing in Difference: Nations, Populations and Genomes

Abstract: This article explores the contemporary scientific practice of human genome science in light of Michel Foucault’s articulation of the problem of population. Rather than transcending the politics of social categories and identities, human genome research mobilizes many different kinds of populations. How then might we aim to avoid overgeneralized readings of the refiguring of human difference in the life sciences and grapple with the multiple and contradictory logics of population classification? In exploring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…If you are 'European' in one instance, you could be 'Caucasian', 'White' or 'Caucasoid' in another even though each permutation bears a different etymology and application, not unsurprising given the intensely contextual nature of how we name and divide ourselves (see Hinterberger, 2012a). As readers will note below, other terms like 'population', 'minorities' or 'ethnicity', are called upon by interviewees to articulate those groups that can be differentiated by the likelihood of having particular HLA frequencies.…”
Section: Finding Racementioning
confidence: 99%
“…If you are 'European' in one instance, you could be 'Caucasian', 'White' or 'Caucasoid' in another even though each permutation bears a different etymology and application, not unsurprising given the intensely contextual nature of how we name and divide ourselves (see Hinterberger, 2012a). As readers will note below, other terms like 'population', 'minorities' or 'ethnicity', are called upon by interviewees to articulate those groups that can be differentiated by the likelihood of having particular HLA frequencies.…”
Section: Finding Racementioning
confidence: 99%
“…Scientific practices involved in research on race and ethnicity in health and genomics have been shown to be situated in and shaped by various specific national, sociopolitical, and historical contexts (Hinterberger, 2012;Epstein, 2010;Tsai, 2010;Olarte Sierra and Díaz Del Castillo Herná ndez, 2014). These national, sociopolitical, and historical contexts shape the ways in which ethnicity and race are enacted in research by prescribing, for example, the (official) categories which must be used in research -a process referred to as ''categorical alignment'' (Epstein, 2007) -or by defining which groups are and are not considered to be ethnic and racial minorities (Gissis, 2008;Helberg-Proctor et al, 2016, 2017Proctor et al, 2011).…”
Section: Researching Ethnicity In the Context Of Healthmentioning
confidence: 99%
“…Consequently, we need to look beyond the prowess of genetic technologies to understand why claims are made about 'uniqueness' or the boundaries of populations. This is borne out by Amy Hinterberger's (2012) analysis of Canadian genomics and the scientific mobilisation of Quebec's founding population, which provides a vivid account of how the "uniqueness" of that population emerged from research driven by European venture capitalists and disseminated by research groups linked to Canadian funding agencies, which depended on enrolment of different types of census categories and registers of national-colonial history. Hinterberger's account of how this genetic population acquired meaning at the nexus of empire, census and multicultural policies in Canada is consistent with our concept of biocoloniality.…”
Section: Introductionmentioning
confidence: 99%